2012
DOI: 10.1590/s1516-89132012000600008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective efficacy of Hypnea muciformis ethanolic extract on CCl4 induced toxicity in rats

Abstract: The ethanolic extract of Hypnea muciformis (red algae) was tested for hepatoprotective activity against experimentally induced liver damage by Carbon tetrachloride (CCl 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Finally, the hepatoprotective activity of red algae extracts has been also indicated to be associated with the prevention of oxidative stress. For instance, the oral administration of Hypnea musciformis ethanolic extract promoted hepatoprotective activity in liver damage-induced rodent models (Bupesh et al 2012). Moreover, similar effects were observed by the polyphenol-enriched extracts from Bryothamnion triquetrum, (Novoa et al 2019), the ethanol extract from Eucheuma cottonii (Wardani et al 2017), and the polysaccharide fraction from Porphyra yezoensis (Guo et al 2007).…”
Section: Other Activitiesmentioning
confidence: 84%
“…Finally, the hepatoprotective activity of red algae extracts has been also indicated to be associated with the prevention of oxidative stress. For instance, the oral administration of Hypnea musciformis ethanolic extract promoted hepatoprotective activity in liver damage-induced rodent models (Bupesh et al 2012). Moreover, similar effects were observed by the polyphenol-enriched extracts from Bryothamnion triquetrum, (Novoa et al 2019), the ethanol extract from Eucheuma cottonii (Wardani et al 2017), and the polysaccharide fraction from Porphyra yezoensis (Guo et al 2007).…”
Section: Other Activitiesmentioning
confidence: 84%
“…Therefore, effective removal of free radicals has been considered one strategy for treatment of liver injury. To achieve this, some natural products from various marine organisms are being investigated as important sources for the prevention of diseases associated with oxidative stress, even though various drugs have already been used in the treatment of hepatic disorders 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 . Recently, several compounds and extracts of the SCT have received a great deal of attention as novel therapeutic mixture candidates because of their antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…www.chinaphar.com Nair DG et al Acta Pharmacologica Sinica npg hepatoprotective activity against CCl 4 -induced liver damage in male albino rats; again, the active compounds involved are not isolated or characterized [30] . Zhao et al demonstrated the antioxidative and hepatoprotective activities of low molecular fucoidan oligosaccharides (LMFO) isolated from Laminaria japonica in mice with liver injury [31] .…”
Section: Previous Reports On Marine-derived Compounds With Hepato Promentioning
confidence: 99%
“…D'Orazio et al, 2012 [34] Takamatsu et al, 2003 [87] Takamatsu et al, 2003 [87] Silva et al, 2012 [88] D'Orazio et al, 2012 [34] Yeh et al, 2012 [89] He et al, 2013 [90] Liu et al, 2012 [47] Esmat et al, 2013 [30] Althunibat et al, 2013 [91] Zhou et al, 2012 [92] Balaji et al, 2004 [45] Pereira et al, 2011 [82] Hong et al, 2012 [93] Liaw et al, 2010 [94] Baidu et al, 2010 [95] Esmat et al, 2013 [33] Whitehouse & Fairlie [96] Kossuga et al, 2008 [97] Kobayashi et al, 2007 [98] Choi et al, 2013 [50] Pinchuk et al, 2013 [51] Tong et al, 2005 [52] Ku et al, 2013 [99] Huang et al, 2007 [100] Posadas et al, 2013 [101] Posadas et al, 2013 [101] Nagle et al, 2004 [102] Catassi et al, 2006 [103] Sun et al, 2007 [39] Kang et al, 2013 [104] Chao et al, 2008 [105] Cheng et al, 2008 [106] …”
mentioning
confidence: 99%